2019
DOI: 10.1016/j.jcjo.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Orbital alveolar soft part sarcoma: case report and literature review

Abstract: Orbital alveolar soft part sarcoma: case report and literature review Alveolar soft part sarcoma (ASPS) is a malignant soft part tissue tumour of uncertain phenotypic expression that mainly affects young adults and children and represents less than 1% of all sarcomas. 1À4 There are only 63 cases of primary orbital ASPS reported in the PUBMED, none from Canada, with a female preponderance and a predilection for affecting the left eye. 1À3 Herein we describe an unusual case of orbital ASPS primary of the orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 13 publications
1
19
1
Order By: Relevance
“…There were 39 males and 45 females. [ 1 2 5 7 8 9 ] Our series showed a male: female ratio of 4:1, contrary to that reported in a majority of the studies. The most common signs were reduced visual acuity, an abaxial proptosis, and restricted extraocular movements.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…There were 39 males and 45 females. [ 1 2 5 7 8 9 ] Our series showed a male: female ratio of 4:1, contrary to that reported in a majority of the studies. The most common signs were reduced visual acuity, an abaxial proptosis, and restricted extraocular movements.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 1 ] Numerous case reports have shown that ASPS is a highly vascular tumor, as seen in three of our cases. [ 5 8 ] This is seen as flow voids on MRI, and in such cases, a preoperative DSA can delineate the vascular supply and major feeder vessels of the tumor. It also guides in planning preoperative embolization to reduce vascularity and intraoperative bleeding, which facilitates a smooth and complete tumor excision.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations